Chitosan–xanthan gum microparticle-based oral tablet for colon-targeted and sustained delivery of quercetin. (November 2014) - Caddeo, Carla; Nácher, Amparo; Díez-Sales, Octavio; Merino-Sanjuán, Matilde; Fadda, Anna Maria; Manconi, Maria
Abstract Context: Quercetin (QUE) is a flavonoid with antioxidant/anti-inflammatory properties, poorly absorbed when orally administered. Objectives: To prepare chitosan/xanthan gum microparticles to increase QUE oral bioavailability and optimize its release in the colon. Materials and methods: Chitosan/xanthan gum hydrogel embedding QUE was spray-dried to obtain microparticles characterized by size, scanning electron microscopy, differential scanning calorimetry and X-ray diffraction. Microparticles were compressed into tablets, coated with Eudragit® to further prevent degradation in acidic pH. The swelling degree and QUE release in simulated gastric and intestinal pH were investigated. Results: Microparticles were smooth and spherical, around 5 µm, with successful QUE loading. Microparticle tablets provided resistance to acidic conditions, allowing complete drug release in alkaline pH, mimicking colonic environment. The release was controlled by non-Fickian diffusion of the dissolved drug out of the swollen polymeric tablet. Discussion and conclusion: Microparticle tablets represent a promising dosage form for QUE delivery to the colon in the oral therapy of inflammatory-based disorders.